An illustrated catalogue of the Neotropical Gracillariidae (Lepidoptera) with new data on primary types - de Prins, Jurate; Arévalo-Maldonado, Helber Adrián; Davis, Donald R.; Landry, Bernard; Vargas, Héctor A.; Davis, Mignon M.; Brito, Rosângela; Fochezato, Júlia; Ohshima, Issei; Moreira, Gilson Rudinei Pires (Zootaxa, 2019)
Gracillariidae leaf miners include 1987 species of poorly studied micromoths for which the majority of the diversity has been described from temperate regions. The Neotropics harbors one of the richest faunas of Gracillariidae, but the rate of taxon descriptions has been slow because of limited sampling and taxonomic activity. In this illustrated catalogue, we provide, for the first time, 476 high resolution illustrations for the 201 species of named gracillariids occurring in the region and revise their classification, newly considering the family-group names Oecophyllembiini stat. nov., Marmarini stat. nov., and Parornichini stat. nov. as tribes of Phyllocnistinae, in the first two cases and Gracillariinae in the last case respectively. Two species, Sauterina hexameris (Meyrick, 1921) comb. nov. and S. phiaropis (Meyrick, 1921) comb. nov., are transferred to Sauterina from Gracillaria. By making taxonomic, distributional, molecular and biological data available in a concise form, we aim to facilitate taxonomic work on Neotropical gracillariids, and in turn to enhance studies in general on poorly studied organisms such as parasitoids from this biogeographical region.